Characterization of microstructure and hardness of friction stir welded brass plate. (2018) - Ramesh, G.; Srimuthunath, I.; Kumar, N. Santha; Sugandipriya, S.; Aravindhan, V.
Abstract: In the present work, the applicability of friction stir welding for the joining of brass plates of 6mm thick was investigated. Friction stir welding process was carried-out with tool rotational speeds 450 and 710 rpm. Lower tool rational speed resulted in formation of visible crack in weld zone whereas smooth defect free weld zone was observed with higher tool rotational speed. Microstructure analysis showed gradual reduction in the grain size from the parent metal to stir zone via the heat affect zone and thermo-mechanically affected zone. Compared to base metal, stir zone showed higher hardness due to fine recrystallized grains.